2008
DOI: 10.3141/2076-09
|View full text |Cite
|
Sign up to set email alerts
|

Social Context of Activity Scheduling

Abstract: Activity-based approaches to travel demand modeling are increasingly moving from theoretical to operational models. Agent-based microsimulation models are a promising approach as they explicitly conceive travel as an emergent phenomenon from people's activity characteristics and, more explicitly, from their activity-scheduling processes. Activity-scheduling processes are influenced by individuals’ characteristics as well as by the people with whom they interact. Thus, the activity-scheduling process has an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The discrete-continuous choice model has been widely used in marketing and economics, especially in energy economics, land economics, and transport economics ( 30 , 3337 ). Many transport decisions involve both discrete and continuous components, for example, household vehicle type and usage ( 3841 ), travel mode/route and departure time ( 4244 ), activity participation and time allocation for activities ( 25 , 45 , 46 ). All of the above examples involve discrete and continuous choices that are interrelated, as the outcome of one clearly affects the other ( 30 ).…”
Section: Modeling Methodologymentioning
confidence: 99%
“…The discrete-continuous choice model has been widely used in marketing and economics, especially in energy economics, land economics, and transport economics ( 30 , 3337 ). Many transport decisions involve both discrete and continuous components, for example, household vehicle type and usage ( 3841 ), travel mode/route and departure time ( 4244 ), activity participation and time allocation for activities ( 25 , 45 , 46 ). All of the above examples involve discrete and continuous choices that are interrelated, as the outcome of one clearly affects the other ( 30 ).…”
Section: Modeling Methodologymentioning
confidence: 99%
“…The process used for making decisions on joint activity-travel choices differs from that used for making decisions on solo activity-travel choices. Joint activity-travel choices require spatiotemporal coordination of the activity-travel schedules of the involved individuals (Zhang et al (2005); Habib et al (2008)). As a result, any change in the daily activity-travel schedule of an individual under a transportation policy can change the daily activity-travel schedules of his/her partners.…”
Section: Background and Motivationmentioning
confidence: 99%
“…In these microsimulation models, the activity-travel choices of individuals have been generated using various approaches, such as computational processes, production rules, and/or utility maximization, to manage the complexity of time-space constraints in intra-household interactions. The activity-travel scheduling processes in these models have typically been based on the concept of skeleton schedules with given and fixed attributes, such as activity start time, duration, destination, and location (Habib et al (2008)). As a result, the linkages in these models between different choice dimensions in households' activitytravel schedules are weak.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to vehicle ownership, these activities are likely to depend on household makeup and sociodemographic variables (16)(17)(18)(19)(20). Further, much recent research has shown that social network variables can also influence social activities (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), including frequency, schedule, distance traveled, destination choice, and duration decisions.…”
Section: Introductionmentioning
confidence: 99%